2016
DOI: 10.1038/npp.2016.97
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: State-Dependent Partial Occlusion of Cortical LTP-Like Plasticity in Major Depression

Abstract: In this article, coauthors Mailies Wirminghaus 1 and Lotte Limbach 1 , whose names were inadvertently omitted from the byline, are now included.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…The reduction of PAS-induced LTP-like plasticity in the motor cortex in MDD before the interventions confirms findings of previous studies ( 2 , 6 ), and different mechanisms may account for this. First, changes in structural and functional synaptic plasticity, such as reduced synaptic density in dorsolateral prefrontal cortex (DLPFC), the anterior corpus callosum (ACC), and the hippocampus ( 5 , 50 , 51 ) are described in MDD, likely leading to reduced functional connectivity within and between networks underlying mood and cognition.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The reduction of PAS-induced LTP-like plasticity in the motor cortex in MDD before the interventions confirms findings of previous studies ( 2 , 6 ), and different mechanisms may account for this. First, changes in structural and functional synaptic plasticity, such as reduced synaptic density in dorsolateral prefrontal cortex (DLPFC), the anterior corpus callosum (ACC), and the hippocampus ( 5 , 50 , 51 ) are described in MDD, likely leading to reduced functional connectivity within and between networks underlying mood and cognition.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies using PAS ( 6 ) and measures of synaptic density ( 5 ) have described an association between the severity of depressive symptoms and neuroplasticity in MDD. We extended these findings in our study by showing that the amount of LTP-like plasticity strongly correlates with the BDI-II scores in both groups at baseline; and further, that the amount of BDI-II score reduction and the increase of PAS plasticity seen after the interventions were correlated in both groups, though stronger in the PA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the early 1900s Sigmund Freud already hypothesized that an alteration of the experience-dependent mechanisms shaping brain networks may be involved in the pathogenesis of mental disorders, describing the neural processes underlying conscious and unconscious memory long before the description of synaptic plasticity [ 185 ]. To date, many clinical reports support this view, since synaptic plastic properties have been found altered in several psychiatric conditions such as Major Depressive Disorder (MDD) [ 186 , 187 ], bipolar disorders [ 188 , 189 ] and schizophrenia [ 190 , 191 ]. Preclinical studies further support the relevance of dysfunctional synaptic transmission in mental disorders, suggesting possible novel synapto-centric therapeutic approaches [ 192 , 193 , 194 , 195 ].…”
Section: Molecular and Electrophysiological Correlates Of Synaptic Dysfunction Underlying Psychiatric Symptoms In Cns Disordersmentioning
confidence: 99%
“…Elevated levels of pro-inflammatory cytokines in the brain also interfere with long-term potentiation (LTP), ,, a synaptic event responsible for strengthening synaptic transmission, which underlies memory formation and learning . LTP is impaired in patients with MDD, which may be a consequence of the elevated levels of proinflammatory cytokines characteristic of depressed individuals. Indeed, studies have demonstrated that peripheral injections of bacterial lipopolysaccharide (LPS), an endotoxin on Gram-negative bacteria that is used to elicit inflammation and produce a rapid elevation of levels of proinflammatory cytokines in circulation, reduce LTP in the hippocampus .…”
Section: Chronic Stress and Proinflammatory Cytokinesmentioning
confidence: 99%